Consecutive Use of the 52 mg Levonorgestrel-releasing Intrauterine System: Variations in Bleeding Patterns - Barbara Zantut Wittmann; Ilza Monteiro; Cássia Juliato; Arlete Fernandes (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective Changes in bleeding patterns could influence the decisions of healthcare professionals to change the levonorgestrel-releasing intrauterine system (LNG-IUS) before 7 years of use, the recommended period of extended use. We evaluated changes in the bleeding patterns of users of the 52 mg LNG-IUS at the end of use of the first (IUS-1) and during the second device (IUS-2) use. Methods We performed an audit of the medical records of all women who used two consecutive LNG-IUSs at the Family Planning clinic. We evaluated the sociodemographic/gynecological variables, the length of use, and the bleeding patterns reported in the reference periods of 90 days before removal of the IUS-1 and at the last return in use of IUS-2. We used the McNemar test to compare bleeding patterns. Statistical significance was established at p < 0.05. Results We evaluated 301 women aged (mean ± SD) 32 (±6.1) years, with lengths of use of 68.9 (±16.8) and 20.3 (±16.7) months for the IUS-1 and IUS-2, respectively. No pregnancies were reported. Bleeding patterns varied significantly among women who used the IUS-2 for ≥ 7 months to 6 years when compared the bleeding patterns reported in IUS-1 use. Eighty-nine out of 221 (40%) women maintained amenorrhea and infrequent bleeding; 66 (30%) evolved to bleeding patterns with light flow, and 66 (30%) maintained or evolved to heavy flow patterns (p = 0.012). No differences were observed among the 80 women with ≤ 6 months of use. Conclusion Changes in bleeding patterns occur during the use of LNG-IUS and should not be decisive for the early replacement of the device.